Gain-of-function mutation in TRPV4 identified in patients with osteonecrosis of the femoral head. Issue 10 (21st June 2016) - Mah, Wayne; Sonkusare, Swapnil K; Wang, Tracy; Azeddine, Bouziane; Pupavac, Mihaela; Carrot-Zhang, Jian; Hong, Kwangseok; Majewski, Jacek; Harvey, Edward J; Russell, Laura; Chalk, Colin; Rosenblatt, David S; et al.
Abstract : Background: Osteonecrosis of the femoral head is a debilitating disease that involves impaired blood supply to the femoral head and leads to femoral head collapse. Methods: We use whole-exome sequencing and Sanger sequencing to analyse a family with inherited osteonecrosis of the femoral head and fluorescent Ca 2+ imaging to functionally characterise the variant protein. Results: We report a family with four siblings affected with inherited osteonecrosis of the femoral head and the identification of a c.2480_2483delCCCG frameshift deletion followed by a c.2486T>A substitution in one allele of the transient receptor potential vanilloid 4 (TRPV4) gene. TRPV4 encodes a Ca 2+ -permeable cation channel known to play a role in vasoregulation and osteoclast differentiation. While pathogenic TRPV4 mutations affect the skeletal or nervous systems, association with osteonecrosis of the femoral head is novel. Functional measurements of Ca 2+ influx through mutant TRPV4 channels in HEK293 cells and patient-derived dermal fibroblasts identified a TRPV4 gain of function. Analysis of channel open times, determined indirectly from measurement of TRPV4 activity within a cluster of TRPV4 channels, revealed that the TRPV4 gain of function was caused by longer channel openings. Conclusions: These findings identify a novel TRPV4 mutation implicating TRPV4 and altered calcium homeostasis in the pathogenesis of osteonecrosis while reinforcing the importance of TRPV4 in bone diseases and vascular endothelium.